PENGEMBANGAN TEORI KEYNESS DALAM JUMLAH KONSUMSI MUSLIM - Muhammad Reza Hermanto (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2015)
The objective of this research is to implement the tought of John Maynard Keynes about consumer behavior and also its antithesis. This study takes muslim as a research subject because Islam as a religion own an institution in order to regulate every muslim in doing consume. This research was expected to find out whether the development of Keynes’s theory (thesis and antithesis) could be implemented in muslim community or not. The variables which used in the model are ammount of consumption (Y), income rate (X1), age (X2), religiosity (X3), and distinguishing community (faculty) as a dummy. Through multiple regression with dummy variable method, from 60 muslim respondents in two different community, was found that income rate (X1) and age (X2) was effected positively and significant to ammount of consumption (Y), religiosity (X3) was effected negatively and significant to ammount of consumption (Y), while dummy variable which is distinguishing community (faculty) was not effected significantly to ammount of consumption (Y). Therefore the dummy variable has dropped out from the research model.DOI: 10.15408/sjie.v4i2.2304